2020
DOI: 10.3390/ijerph17093101
|View full text |Cite
|
Sign up to set email alerts
|

“Coach Really Knew What I Needed and Understood Me Well as a Person”: Effective Communication Acts in Coach–Athlete Interactions among Korean Olympic Archers

Abstract: The purpose of this study is to qualitatively explore situations in which athletes perceived communication with their coach to be important and determine the effect of this communication on the athletes. Literature on the communication process in sports emphasizes the distinct characteristics of each sports and its setting. However, previous research has not studied various settings in detail, and archery is yet to be explored. The qualitative process included an in-depth, semi-structured interview with eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 45 publications
(54 reference statements)
1
9
0
1
Order By: Relevance
“…Meanwhile, athletes' autonomy-supportive coaches may also explain these positive results. In an in-depth interview with Korean Olympic archers, several players stated that when their coach supported the goals they decided to pursue and gave them permission to express their views about the training schedule, they felt more dedicated and accountable to achieve their set goals (Kim and Park, 2020). This finding corroborates our results, demonstrating that commitment can significantly and positively be affected by athletes' control over their training environment and interpersonal communication with their coach.…”
Section: Self-management and Outcome Variables In Different Martial Arts Sportssupporting
confidence: 86%
“…Meanwhile, athletes' autonomy-supportive coaches may also explain these positive results. In an in-depth interview with Korean Olympic archers, several players stated that when their coach supported the goals they decided to pursue and gave them permission to express their views about the training schedule, they felt more dedicated and accountable to achieve their set goals (Kim and Park, 2020). This finding corroborates our results, demonstrating that commitment can significantly and positively be affected by athletes' control over their training environment and interpersonal communication with their coach.…”
Section: Self-management and Outcome Variables In Different Martial Arts Sportssupporting
confidence: 86%
“…Specifically, how coaches prepare working strategies and how the team is oriented from a technical point-of-view is determinant of increased athlete and team confidence and performance (Almeida et al, 2019;Keatlholetswe and Malete, 2019). In this regard, the coach needs to master communication skills since it has been reported previously to be associated with athlete and team accomplishments (Kim and Park, 2020;Moll and Davies, 2021). Coaches' ability to communicate effectively is critical since all tasks related to athlete top performance requires high communication skills from coaches (Gomes et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, Hague et al (2021) have indicated that there is still a need for more research related to the technical information inherent in sport coaching. Thus, how coaches communicate feedback and technical strategies as a mean to maximize athlete's abilities is a key aspect that needs more investigation (Kim and Park, 2020). The coaching behavior is a combination of previously made decisions and reflexive thinking (Moreno and Alvarez, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perceived social support further reinforces the safety of athletes, which has been widely analyzed in previous research that describes the manifestations of bullying, harassment, and abuse as a result of the support and concern of coaches regarding athletes and their sports performance [ 39 ]. On the other hand, attachment with coaches is extremely important [ 21 , 40 ]. Coaches provide athletes with a growth platform, and encourage them to face new challenges and develop new skills.…”
Section: Introductionmentioning
confidence: 99%